Development of a Simple and Practical Screening Tool for Detection of Sarcopenia in Older People: The Bushehr Elderly Health Program - Shafiee, Gita; Ostovar, Afshin; Maleki Birjandi, Saba; Nabipour, Iraj; Larijani, Bagher; Heshmat, Ramin (Frontiers in Medicine, 2021)
Background: Sarcopenia is defined by the loss of muscle mass and function with a considerable prevalence which increases morbidity and mortality. We aimed to develop and validate a simple tool for screening of sarcopenia in Iranian older population. Methods: In this study, we included 2,211 adults aged 60 years or older that participated in the stage II of Bushehr Elderly Health (BEH) program, a population-based prospective cohort study. We defined sarcopenia as reduced skeletal muscle strength plus low muscle mass. The study sample was divided into two parts; development set which were allocated to the development of the model (n=1499) and validation set (n=712) were allocated to validation of the model. Results: There were 22.9% of men and 23.2% women classified as having sarcopenia based on EWGSOP-2.After selection of variables, the final models named SarSA-Mod (Sarcopenia Scoring Assessment Models) were developed with area to under curves (AUC) of 0.82 (0.79-0.86) and 0.87 (0.84-0.90) in men and women, respectively. The final model included “age”, “weight” and “calf circumference” in both sexes. The sensitivity and specificity and positive and negative predictive values for sarcopenia were 84.3% , 76.0%, 49.8 % and 94.5% for women, 85.4%, 64.8%, 40.2% and 94.2% for men, respectively. The model performance was tested in the validation set with accuracy 91% and 84% among women and men, respectively. Conclusions: Sarcopenia could be detected using SarSA-Mod, as a simple screening test with high accuracy among both sexes. Also, this screening test is valid, feasible, reliable and cost-effective compared to other tools.